Morpho-hydrology and classification of Sayaligad River, Doti district, lesser Himalaya (Journal of Nepal Geological Society, 2025)
The Sayali Gad (River) basin is an elongated crocodile-shaped basin having an area of 185 sq. km. The rugged topography of the basin makes it vulnerable to mass wasting and flooding. The relative relief is highest at the north-facing side of Sau Khola gaon and Silla village and lowest at the source area, Khaptad. The drainage density, drainage texture, and stream frequency value are higher in the source area and on the north-facing slope. The Sayali Gad is a fifth-order stream that flows from east to west and is a tributary of the Seti Nadi. The 24 km long segment of the fifth-order stream is taken for study, and the morpho-hydrologic parameters were studied within 2 km intervals. The stream types at T1 is B3a, at T2 is A3a+, T3 is B3a, T4 is E2b, T5 is C3b, T6 is C2b, at T7 is B4, at T8 is C4c, T9 is E4b, T10 is C4 and T11 is also C4. The transect T2 is entrenched, T1, T3 and T7 are moderately entrenched and the transect T4, T5, T6, T8, T9, T10, T11 is slightly entrenched. The river is vertically unstable at the upstream portion and laterally unstable at the downstream.